Characterization of host-dependent mutations of apple fruit crinkle viroid replicating in newly identified experimental hosts suggests maintenance of stem-loop structures in the left-hand half of the molecule is important for replication - Suzuki, Takahiro; Fujibayashi, Misato; Hataya, Tatsuji; Taneda, Akito; He, Ying-Hong; Tsushima, Taro; Duraisamy, Ganesh Selvaraj; Siglová, Kristyna; Matoušek, Jaroslav; Sano, Teruo (Journal of general virology, 2017)
Apple fruit crinkle viroid (AFCVd) is a tentative member of the genus Apscaviroid, family Pospiviroidae. AFCVd has a narrow host range and is known to infect apple, hop and persimmon as natural hosts. In this study, tomato, cucumber and wild hop have been identified as new experimental herbaceous hosts. Foliar symptoms were very mild or virtually undetectable, but fruits of infected tomato were small, cracked and distorted. These symptoms resemble those observed on some AFCVd-sensitive apple cultivars. After transfer to tomato, cucumber and wild hop, sequence changes were detected in a natural AFCVd isolate from hop, and major variants in tomato, cucumber and wild hop differed in 10, 8 or 2 nucleotides, respectively, from the predominant one in the inoculum. The major variants in tomato and cucumber were almost identical, and the one in wild hop was very similar to the one in cultivated hop. Detailed analyses of the host-dependent sequence changes that appear in a naturally occurring AFCVd isolate from hop after transfer to tomato using small RNA deep sequence data and infectivity studies with dimeric RNA transcripts followed by progeny analysis indicate that the major AFCVd variant in tomato emerged by selection of a minor variant present in the inoculum (i.e. hop) followed by one to two host-dependent de novo mutations. Comparison of the secondary structures of major variants in hop, tomato and persimmon after transfer to tomato suggested that maintenance of stem-loop structures in the left-hand half of the molecule is critical for infection.
Keywords: Solanum lycopersicum; RNA virová; Plant Viruses; Host-Pathogen Interactions; rostlinné viry; Plant Diseases; interakce hostitele a patogenu; viroidy; Humulus; mutace; Virus Replication; Cucumis sativus; Viroids; nemoci rostlin; konformace nukleové kyseliny; replikace viru; RNA, Viral; Nucleic Acid Conformation; Mutation; Diospyros; obrácené repetice; Inverted Repeat Sequences